Integration Model of Primary and Referral Services in Catastrophic Emergency Management at Grandmed General Hospital Lubuk Pakam in 2023 - Wenny Dwi Chandra (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Catastrophic emergencies require effective integration between primary care and referral services to accelerate patient management. However, the implementation of the referral system in Indonesia still faces challenges, including limited infrastructure, human resources, and inter-facility coordination. Objective: This study aimed to analyze and develop an integrated model of primary care and referral services in the management of catastrophic emergencies at RSU Grandmed Lubuk Pakam in 2023. Methods: A mixed-method approach with a sequential explanatory design was applied. Quantitative data were collected through questionnaires distributed to 80 healthcare workers involved in the referral process, while qualitative data were obtained from in-depth interviews and focus group discussions with 15 key informants. Quantitative data were analyzed using descriptive and inferential statistics, whereas qualitative data were analyzed thematically. Results: Findings revealed that ambulance availability was considered adequate (70%), while emergency equipment (55%) and digital communication systems (40%) remained limited. Most healthcare workers had received emergency training (62.5%), yet only 48% felt confident in referral coordination. The referral process was relatively clear (60%), but inter-facility coordination (45%) and patient data integration (35%) were suboptimal. Qualitative analysis highlighted four main issues: weak integrated communication, limited trained human resources, the need for digitalization of the referral system, and insufficient cross-sector coordination. Conclusion: This study proposes an integration model consisting of four key components: (1) strengthening infrastructure, (2) enhancing healthcare workers’ capacity through training and simulations, (3) implementing an application-based referral information system, and (4) reinforcing cross-sector coordination. This model is expected to improve the effectiveness of catastrophic emergency management at RSU Grandmed Lubuk Pakam and serve as a reference for other hospitals in Indonesia